The transition to adult income supports for youth that received special education in British Columbia, Canada: A cohort study. (16th May 2022) - Russell, Matthew Joseph; Scott, Craig William Michael; Berrigan, Patrick; Murias, Kara; Gibbard, W. Ben; Cui, Xinjie; Tough, Suzanne; Zwicker, Jennifer D.
Abstract: Youth in special education have complex needs that are supported across multiple systems. Our research investigates the use of adult income assistance, as one structure that supports youth as they transition to adulthood. We created a cohort of youth (5–22 years old) using linked administrative data from British Columbia government ministries from 1996 to 2018. Youth were grouped by their special education funding (most to least; Level 1, Level 2, Level 3, Unfunded, and no special education). We investigated (1) youth characteristics and service use patterns, (2) which youth used income supports after the child‐to‐adult transition (19–22 years old), and what youth characteristics and service use patterns were associated with use, and (3) how much income support they used (CAD). Of 174, 527 youth, 254 (0.1%) were Level 1, 6020 (3.4%) were Level 2, 4409 (2.5%) were Level 3, 21, 232 (12.2%) were Unfunded, and 142, 612 (81.7%) were not in special education. Youth assigned higher funding levels, compared to lower levels, generally had increased service use, and in the transition to adult services were more likely to use income supports, and received more income support. An important exception was youth with serious behavioural/mental health special education funding (Level 3), who had increased service use for their level of funding, but received less income support due to a reliance on Temporary versus Disability Assistance. Youth that received an accredited diploma were less likely to use income supports. Factors related to the use of income supports are further described. This study highlights differences in access to income support when youth transition to adult services and considerations around equitable access to support.